Degradasi Asam Humat Pada Air Rawa Gambut menggunakan Metode Fotosonolisis dengan Bantuan Katalis ZnO - Alfindri Zulkarnaini; Hary Sanjaya; Yohandri Yohandri; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2022)
Photosonolysis method can be used to degrade humic acid in peat swamp water with the help of ZnO catalyst. This study aims to determine the effect of time variation and catalyst variation on peat swamp degradation. UV-Vis spectrophotometer was used to calculate the absorbance concentration of peat swamp air before and before degradation. The results showed that the highest percentage of peat swamp water degradation was 26.81% at 120 minutes using a ZnO catalyst. The highest degradation of peat swamp water was at 21.99% with a mass catalyst of 0.3 grams of ZnO